New Attacks on SARI Image Authentication System - Wu, J.; Zhu, Bin Benjamin; Li, S.; Lin, F. (International Society for Optical Engineering, 2004)
The image authentication system SARI proposed by Lin and Chang passes JPEG compression and rejects other malicious manipulations. Some vulnerabilities of the system have been reported recently. In this paper, we propose two new attacks that can compromise the SARI system. The first attack is called a histogram attack which modifies DCT coefficients yet maintains the same relationship between any two DCT coefficients and the same mean values of DCT coefficients. Such a modified image can pass the SARI authentication system. The second attack is an oracle attack which uses an oracle to efficiently find the secret pairs used by SARI in its signature generation. A single image plus an oracle is needed to launch the oracle attack. Fixes to thwart the proposed attacks are also proposed in this paper.